TRAINING OF ORGANIC VEGETABLE CULTIVATION TO DEVELOP STUDENTS' ENTREPRENEURIAL SPIRIT IN PROBOLINGGO REGENCY - Cahyanto, Bagus; Faliyandra, Faisal; Angga Rini, Titis; Luh Sakinah Nuraini, Ni Luh Sakinah Nuraini (Prestise: Jurnal Pengabdian Kepada Masyarakat Bidang Ekonomi dan Bisnis, 2025)
The community service activity aims to foster an entrepreneurial spirit among students and strengthen school independence in developing entrepreneurship programs based on local potential. The training activity was carried out at SMPN 4 Lumbang, Probolinggo Regency. The stages of this training activity include planning that includes identifying partner needs, preparing training designs, implementing training, and evaluating and following up through questionnaires, interviews, and participant work portfolios. The results of the training showed an increase in participants' conceptual understanding of entrepreneurial principles, technical skills in organic vegetable cultivation, and motivation to start a business independently. In addition, this training activity also formed an organic vegetable garden at the school as an entrepreneurship laboratory. The benefits of this activity are not only felt by the participants but on the other hand it is also able to strengthen the development of teacher and institutional capacity in developing entrepreneurship-based programs in the school environment. Recommendations for the future are that schools can develop collaboration with farmers and MSMEs while integrating entrepreneurial values ​​into the school curriculum so that the development of entrepreneurship among students can run optimally.